2023
DOI: 10.2113/gsjfr.53.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Microfaunal Recording of Recent Environmental Changes in the Herschel Basin, Western Arctic Ocean

Abstract: Microfaunal assemblages of benthic foraminifera, ostracods, and tintinnids from two marine sediment cores retrieved from the Herschel Basin of the Canadian Beaufort Sea shelf document relationships with environmental parameters such as salinity, sea-ice cover, and turbulence. Cores YC18-HB-GC01 and PG2303-1 were collected at 18 and 32 m water depth, respectively. At these sites, sediment accumulation rates range between 0.6 and 1.7 cm yr–1 allowing a near-annual temporal resolution over the last 50 years. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 105 publications
2
14
0
Order By: Relevance
“…The age models were defined based on radiometric analyses, combining 210 Pb, 226 Ra, 137 Cs and 14 C measurements; fore core PG2303 all methods were used, while for PG2303-1 we concentrated on 210 Pb, 226 Ra, and 137 Cs. The age model for PG2303-1 has previously been presented by Falardeau et al (2023), who showed that the bottom of this core may be dated to 1999 ± 6 CE.…”
Section: Radiometric Chronologymentioning
confidence: 82%
See 4 more Smart Citations
“…The age models were defined based on radiometric analyses, combining 210 Pb, 226 Ra, 137 Cs and 14 C measurements; fore core PG2303 all methods were used, while for PG2303-1 we concentrated on 210 Pb, 226 Ra, and 137 Cs. The age model for PG2303-1 has previously been presented by Falardeau et al (2023), who showed that the bottom of this core may be dated to 1999 ± 6 CE.…”
Section: Radiometric Chronologymentioning
confidence: 82%
“…S1). The 12.3 m long core was collected in 32 m water depth at 69.513 • N and 138.895 • W in clastic mud (Falardeau et al, 2023). The sediment record is constructed as a composite sequence of five overlapping core segments that were correlated based on magnetic susceptibility (Pfalz, 2017).…”
Section: Sediment Coresmentioning
confidence: 99%
See 3 more Smart Citations